Humanization in the Intensive Care: perception of family and healthcare professionals - Flavia Feron Luiz; Rita Catalina Aquino Caregnato; Márcia Rosa da Costa
ABSTRACT Objective: Understanding perceptions of family members and healthcare professionals about humanization at the Intensive Care Unit (ICU) to direct it to an educational action. Method: Exploratory descriptive and qualitative study conducted in an ICU level 3 of a public hospital in Porto Alegre, RS, Brazil, with fourteen subjects, eight family members and six healthcare professionals. Data collection carried out through semi-structured interviews and focus group. Content Analysis was used. Results: Emerged categories were: welcoming; communication; ethical and sensible professionalism; unfavorable aspects; perception on humanization; and religiosity/spirituality. Final considerations: Although the subjects have expressed their perceptions about humanization in different ways, both groups pointed out the same needs and priorities to improve humanization in Intensive Care. From the results, we created a reflective manual of humanizing assistance practices for professionals, a board to facilitate communication of these professionals with patients and a guideline book for family members.